ENGOs and climate change: a systematic review of their evolving roles and influencing factors - Jiao, Yijuan; Huang, Zhicang; Du, Hongrong; Duan, Kai; Tan, Mou Leong (Frontiers in Environmental Science, 2026)
IntroductionAs global climate action accelerates, there is a growing need for systematic evidence on the roles of Environmental Non-Governmental Organizations (ENGOs) in climate governance and the factors shaping their participation. Although ENGOs are widely recognized as key non-state actors, the existing literature remains fragmented, with limited integrative analysis of how their roles are evolving across different governance levels and policy contexts.MethodsThis study conducts a systematic literature review following the PRISMA framework, examining 36 peer-reviewed articles published between 2015 and 2025 and retrieved from the Web of Science and Scopus databases. Bibliometric analysis using Bibliometrix and VOSviewer is combined with inductive content analysis to identify dominant research trends, key influencing factors, and evolving governance roles of ENGOs.ResultsThe review identifies five primary factors shaping ENGO participation in global climate governance: institutional and policy environments, resource and financial support, scientific and technical capacity, social networks and alliances, and public participation and legitimacy. Influenced by these factors, ENGOs are transitioning from traditional roles focused on service delivery and advocacy toward strategic policy coordination, the provision of technical and digital governance support, the construction of decentralized governance networks, engagement with economic mechanisms, and an increased emphasis on climate justice. The literature further highlights a growing reliance on digital tools and transnational partnerships, alongside persistent regional imbalances, with research and governance influence concentrated in Europe and North America.DiscussionThese findings indicate that ENGOs are increasingly functioning as system integrators within polycentric climate governance structures. However, enduring challenges remain, including North–South disparities, tensions between global coordination and local accountability, and uncertainties regarding appropriate governance scales. Future research should prioritize comparative, multi-level, and cross-regional analyses, and strengthen capacity-building and collaboration in the Global South to enhance the effectiveness and equity of ENGO contributions to global climate governance.